Analysis of Challenges and Strategies for the Development of Sharia Financial Services Cooperatives (Case Study of the Abdi Kerta Raharja Sharia Savings and Loans and Financing Cooperative (KSPPS) in Tangerang Regency) - Heriyadi, Dedi; Amrizal, Amrizal (Budapest International Research and Critics University, 2024)
The purpose of the study was to determine the dimensions of savings and loans and financing in the Abdi Kerta Raharja (AKR) sharia cooperative in the Tangerang district, to evaluate and examine the challenges faced by the Abdi Kerta Raharja Islamic savings and loan cooperatives in the Tangerang district and to apply a model of the savings and loan development and sharia financing strategy that is right at the Abdi Kerta Raharja sharia cooperative in Tangerang district. The survey method in this research is a qualitative research type with a descriptive approach. Data collection techniques with semi-structured insight guidelines. The results of the study show that the savings and loans and financing of Kopsyah AKR clearly and significantly turns out to be